1998
DOI: 10.1086/647721
|View full text |Cite
|
Sign up to set email alerts
|

Does Clinical Experience Affect Medical Students' Knowledge, Attitudes, and Compliance With Universal Precautions?

Abstract: Jeffe, Donna B.; Mutha, Sunitha; Kim, Lynn E.; Evanoff, Bradley A.; L'Ecuyer, Paul B.; and Fraser, Victoria J., "Does clinical experience affect medical students' knowledge, attitudes, and compliance with universal precautions?".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Social distancing can help reduce the peak incidence of an epidemic and spread it over several weeks instead of a few, thus avoiding a healthcare surge ( 6 ). Household quarantine is also effective at reducing attack rates in the community but only if the compliance rate is high ( 7 ). Knowledge regarding treatment of pandemic influenza is difficult to analyze because determining what measures would be effective is complex.…”
Section: Discussionmentioning
confidence: 99%
“…Social distancing can help reduce the peak incidence of an epidemic and spread it over several weeks instead of a few, thus avoiding a healthcare surge ( 6 ). Household quarantine is also effective at reducing attack rates in the community but only if the compliance rate is high ( 7 ). Knowledge regarding treatment of pandemic influenza is difficult to analyze because determining what measures would be effective is complex.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the participants in these studies were qualified nurses or doctors and all the research was hospital-based. One study involved student nurses (Wang et al 2003), and three studies monitored medical students (Diekema et al 1995, Jeffe et al 1998, 1999. All of the studies applied a quantitative design, generally two groups of subjects and involved reassessment of compliance postintervention.…”
Section: Practice Innovations To Improve Compliancementioning
confidence: 99%
“…Community Health was the second preferred specialisation, which is indeed a finding unique to this study; previous studies in India having reported Community Physiotherapy as a neglected profession (Rajan, 2012(Rajan, , 2013. This could again be due to the opportunities that students have at this particular training institute, to gain knowledge and foster their interests (Jeffe et al, 1998;Latimer et al, 2004). Therefore, such models could be replicated in other institutes to help increase the number of students interested in working as community physiotherapists.…”
Section: Discussionmentioning
confidence: 99%
“…The year of the programme plays an important role in the understanding of the student (Jeffe et al, 1998). In the study by Jeffe et al (1998), a comparison was done between second, third and final year students in a medical school in the United States. The authors concluded that the timing of introduction of concepts is important as it affects the attitude towards and knowledge about a particular subject.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation